2011
DOI: 10.1186/1471-2164-12-34
|View full text |Cite
|
Sign up to set email alerts
|

Divergent responses to peptidoglycans derived from different E. coli serotypes influence inflammatory outcome in trout, Oncorhynchus mykiss, macrophages

Abstract: BackgroundPathogen-associated molecular patterns (PAMPs) are structural components of pathogens such as lipopolysaccharide (LPS) and peptidoglycan (PGN) from bacterial cell walls. PAMP-recognition by the host results in an induction of defence-related genes and often the generation of an inflammatory response. We evaluated both the transcriptomic and inflammatory response in trout (O. mykiss) macrophages in primary cell culture stimulated with DAP-PGN (DAP; meso-diaminopimelic acid, PGN; peptidoglycan) from tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 85 publications
2
17
0
Order By: Relevance
“…Fish cage culture is a highly efficient intensive system that is a potentially stressful environment due to overcrowding, inducing fish susceptibility to pathogen infection due to immune system alterations, which may result in fish disease (Villamil et al, 2003). In recent years, immunostimulants have been included in the feed of cultured fish in order to improve their immune system (Meena et al, 2013;De et al, 2014;Vaseeharan & Thaya, 2014;Yang et al, 2016), stress resistance, antioxidant activity (Zhao et al, 2012;Guzmán-Villanueva et al, 2014;Zanuzzo et al, 2015;Zeng et al, 2016), inflammatory response (Boltaña et al, 2011), and resistance to bacterial (Bonaldo et al, 2009;Meshram et al, 2015), virus (Parmar et al, 2012) and parasite infections (Jaafar et al, 2011). Glucans are polysaccharides with different primary molecular structures that vary depending on their source, which have different implications on their immunostimulant activity (Akramienė et al, 2007); glucans are commonly found ___________________ Corresponding editor: Jesús Ponce-Palafox in mushrooms, algae, yeast, cereals and cell walls of bacteria (Ringø et al, 2011;Meena et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Fish cage culture is a highly efficient intensive system that is a potentially stressful environment due to overcrowding, inducing fish susceptibility to pathogen infection due to immune system alterations, which may result in fish disease (Villamil et al, 2003). In recent years, immunostimulants have been included in the feed of cultured fish in order to improve their immune system (Meena et al, 2013;De et al, 2014;Vaseeharan & Thaya, 2014;Yang et al, 2016), stress resistance, antioxidant activity (Zhao et al, 2012;Guzmán-Villanueva et al, 2014;Zanuzzo et al, 2015;Zeng et al, 2016), inflammatory response (Boltaña et al, 2011), and resistance to bacterial (Bonaldo et al, 2009;Meshram et al, 2015), virus (Parmar et al, 2012) and parasite infections (Jaafar et al, 2011). Glucans are polysaccharides with different primary molecular structures that vary depending on their source, which have different implications on their immunostimulant activity (Akramienė et al, 2007); glucans are commonly found ___________________ Corresponding editor: Jesús Ponce-Palafox in mushrooms, algae, yeast, cereals and cell walls of bacteria (Ringø et al, 2011;Meena et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, rainbow trout macrophages stimulated with PGN induced the expression of Myd88, IRAK and a TNF‐activated factor (TRAF6), suggesting the involvement of TLR in PGN‐mediated inflammatory responses in trout (Boltaña et al . ). However, although knowledge regarding the TLR‐mediated fish innate immune response is increasing, further investigation is necessary to determine the underlying effects upon recognition and activation of the fish immune response by PAMP‐associated immunostimulants.…”
Section: Immunostimulatory Activities Of Cellular Componentsmentioning
confidence: 97%
“…Likewise, in contrast to LPS from other Salmonella species, LPS from S. typhimurium moderately enhances proliferation of Tregs . Furthermore, PGN originating from distinct strains of E. coli has been found to induce distinct transcriptional responses in trout macrophages . Thus, intestinal PRRs have the potential to specifically recognize microbe safety signals of certain species of bacteria.…”
Section: Symbiosis Depends On Immune Tolerancementioning
confidence: 99%